Malaria vaccines: Past, present and future - Von Seidlein, L; Bejon, P (2013)
The currently available malaria control tools have allowed malaria elimination in many regions but there remain many regions where malaria control has made little progress. A safe and protective malaria vaccine would be a huge asset for malaria control. Despite the many challenges, efforts continue to design and evaluate malaria vaccine candidates. These candidates target different stages in the life cycle of Plasmodia. The most advanced vaccine candidates target the pre-erythrocytic stages in the life cycle of the parasite and include RTS, S/AS01, which has progressed through clinical development to the stage that it may be licensed in 2015. Attenuated whole-parasite vaccine candidates are highly protective, but there are challenges to manufacture and to administration. Cellular immunity is targeted by the prime-boost approach. Priming vectors trigger only modest responses but these are focused on the recombinant antigen. Boosting vectors trigger strong but broad non-specific responses. The heterologous sequence produces strong immunological responses to the recombinant antigen. Candidates that target the blood stages of the parasite have to result in an immune response that is more effective than the response to an infection to abort or control the infection of merozoites and hence disease. Finally, the sexual stages of the parasite offer another target for vaccine development, which would prevent the transmission of malaria. Today it seems unlikely that any candidate targeting a single antigen will provide complete protection against an organism of the complexity of Plasmodium. A systematic search for vaccine targets and combinations of antigens may be a more promising approach.